The impact of self-isolation on psychological wellbeing in adults and how to reduce it: A systematic review - Alex F. Martin; Louise E. Smith; Samantha K. Brooks; Madeline V. Stein; Rachel Davies; Richard Amlôt; Neil Greenberg; Gideon James Rubin (PLoS ONE, 2025)
Objective To synthesise evidence on the impact of self-isolation at home on the psychological and emotional wellbeing of adults in the general population during the COVID-19 pandemic. Methods This systematic review was registered on PROSPERO (CRD42022378140). We searched Medline, PsycINFO, Web of Science, Embase, and grey literature. Wellbeing included adverse mental health outcomes and adaptive wellbeing. We followed PRISMA and synthesis without meta-analysis (SWiM) guidelines. We extracted data on the impact of self-isolation on wellbeing, and factors associated with and interventions targeting wellbeing during self-isolation. Results Thirty-six studies were included. The mode quality rating was ‘high-risk’. Depressive and anxiety symptoms were most investigated. Evidence for an impact of self-isolation on wellbeing was often inconsistent in quantitative studies, although qualitative studies consistently reported a negative impact. People with pre-existing mental and physical health needs reported increased symptoms of mental ill health during self-isolation. Studies reported modifiable stressors that have been reported in previous infectious disease contexts, such as inadequate support, poor coping strategies, inadequate and conflicting information, and highlighted the importance of regular contact from trusted healthcare professionals. Interventions targeting psychological wellbeing were rare and evaluative studies of these had high or very high risk of bias. Conclusion When implementing self-isolation directives, public health officials should prioritise support for individuals who have pre-existing mental or physical health needs, lack support, or who are facing significant life stressors. Focus should be directed toward interventions that address loneliness, worries, and misinformation, whilst monitoring and identifying individuals in need of additional support.